Peripheral Inflammatory Markers and Antioxidant Response during the Post-Acute and Chronic Phase after Severe Traumatic Brain Injury - Licastro, Federico; Hrelia, Silvana; Porcellini, Elisa; Malaguti, Marco; Di Stefano, Cristina; Angeloni, Cristina; Carbone, Ilaria; Simoncini, Laura; Piperno, Roberto (Frontiers in Neurology, 2016)
Traumatic brain injury (TBI) is a mechanical insult to the brain caused by external forces and associated with inflammation and oxidative stress. The patients may show different profiles of neurological recovery and a combination of oxidative damage and inflammatory processes can affect their courses. It is known that an over-expression of cytokines can be seen in peripheral blood in the early hours/days after the injury, but little is known about the weeks and months encompassing the post-acute and chronic phases. In addition, no information is available about the antioxidant responses mediated by the major enzymes that regulate ROS levels: superoxide dismutase (SOD), catalase (CAT), peroxidases, and GSH related enzymes. This study investigates the 6-month trends of inflammatory markers and antioxidant responses in 22 severe TBI patients with prolonged disorders of consciousness, consecutively recruited in a dedicated neuro-rehabilitation facility. Patients with a high degree of neurological impairment often show an uncertain outcome. In addition, the profiles of plasma activities were related to the neurological recovery after 12 months. Venous peripheral blood samples were taken blindly as soon as clinical signs and laboratory markers confirmed the absence of infections, 3 and 6 months later. The clinical and neuropsychological assessment continued up to 12 months. Nineteen patients completed the follow up. In the chronic phase, persistent high plasma levels of cytokines can interfere with cognitive functioning and higher post-acute levels of cytokines (IFN-g, TNF-a, IL1b, IL6) are associated with poorer cognitive recoveries 12 months later. Moreover, higher IFN- γ, higher TNF-α and lower glutathione peroxidase (GPx) activity are associated with greater disability. The results add evidence of persistent inflammatory response, provide information about long-term imbalance of antioxidant activity and suggest that the over-production of cytokines and the alteration of the redox homeostasis in the post-acute phase might adversely affect the neurological and functional recovery. Inflammatory and antioxidant activity markers might offer a feasible way to highlight some of the processes opposing recovery after a severe TBI.